The fierceness of fronted /s/: Linguistic rhematization through visual transformation - Calder, Jeremy (Language in Society, 2019)
This article explores the roles that language and the body play in the iconization of cross-modal personae (see Agha 2003, 2004). Focusing on a community of radical drag queens in San Francisco, I analyze the interplay of visual presentation and acoustic dimensions of /s/ in the construction of the fierce queen persona, which embodies an extreme, larger-than-life, and anti-normative type of femininity. Taking data from transformations—conversations during which queens visually transform from male-presenting into their feminine drag personae—I explore the effect of fluid visual presentation on linguistic production, and argue that changes in both the linguistic and visual streams increasingly invoke qualia (see Gal 2013; Harkness 2015) projecting ‘harshness’ and ‘sharpness’ in the construction of fierce femininity. I argue that personae like the fierce queen become iconized through rhematization (see Gal 2013), a process in which qualic congruences are construed and constructed across multiple semiotic modalities. (Iconization, rhematization, qualia, sociophonetics, gender, personae, drag queens)*
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; drag queen; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; san francisco; sciences humaines; thématiques; états-unis

Góor-jigéen: la resignification négative d’une catégorie entre genre et sexualité (Sénégal) - Christophe Broqua (Socio, 2019)
Dans de nombreux pays africains, il a existé et il existe encore parfois des figures institutionnalisées de la diversité de genre. C’est le cas, au Sénégal, du góor-jigéen, littéralement « homme-femme » en langue wolof. Évoquée dans certains récits d’observateurs dès le xixe siècle, cette figure a rarement été décrite ou analysée avec précision dans la littérature savante. Pendant longtemps, le góor-jigéen était un homme biologique présentant des attributs féminins et occupant préférentiellement certaines fonctions sociales. Son statut et sa place étaient reconnus au sein de la société sénégalaise. Progressivement, l’expression est devenue synonyme d’homosexuel masculin et elle est aujourd’hui le plus souvent utilisée comme une injure. Elle a donc connu une « resignification négative », traduisant la transformation d’une catégorie de genre en une catégorie d’orientation sexuelle. Cet article retrace l’histoire de la figure du góor-jigéen et analyse les conditions qui ont rendu possible la transformation de sa signification et de sa position sociales.
Keywords: LGBTQIA2+; afrique; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; premier cycle; queer; ressource en ligne; régions géographiques; sciences humaines; sénégal; thématiques

Trans self-identification and the language of neoliberal selfhood: Agency, power, and the limits of monologic discourse - Zimman, Lal (International Journal of the Sociology of Language, 2019)
Sociocultural linguists share with transgender communities a strong interest in the power of individuals to assert agency over linguistic patterns. For trans people, a key principle of activism is gender self-determination, which treats each individual as the ultimate authority on their own gender identity. This article explores some of the ways gender self-determination and self-identification surface in transgender people’s linguistic practices. Three particular manifestations are highlighted: gendered identity labels, third person pronouns, and body part terminology. The observations offered on these subjects are based on a series of ethnographic projects carried out from 2006–2016 in transgender communities across several metropolitan areas in the United States and in online spaces frequented by trans people. However, the analysis goes beyond mere description by treating this kind of individualized linguistic agency as the product of cultural practice rather than an asocial given. Such a perspective introduces questions concerning why this form of agency arose in the time and place that it has. This article frames gender self-identification as an enactment of neoliberal personhood, in which individuals are framed as the driver of their destiny. What the ideology of neoliberal agency obscures, however, is that agency is not an equally distributed resource.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; agentivité; amériques; approches et analyses; cours; discipline; identités LGBTQIA2+; lin2685; linguistique; néolibéralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sofia; thématiques; transféminisme; états-unis

The Oxford handbook of language and sexuality - Hall, Kira; Barrett, Rusty (Oxford University Press, 2018)
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; outils; ouvrages de références; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; sociolinguistique; thématiques

Language and masculinities: performances, intersections, dislocations - Milan, Tommaso M. (Routledge critical studies in discourse, 2015)
This volume showcases cutting-edge research in the linguistic and discursive study of masculinities, comprising the first significant edited collection on language and masculinities since Johnson and Meinhof’s 1997 volume. Overall, the chapters are linked together by a critical analytical perspective that seeks to understand the relationships between discourse, masculinities, and power. Whereas some of the chapters offer detailed, linguistically informed critiques of the ways in which old and new expressions of masculinities are complicit in the reproduction of men’s hegemonic positions of power, others provide a more complex picture, one in which collusion and subversion go hand in hand. Contributions argue for the need for research on language and masculinities to expand its remit so as to engage with "gay masculinities," and unsettle gendered categories in order to consider the ways in which women, transgender, and intersex individuals also perform a variety of masculinities. Finally, unlike Johnson and Meinhof’s 1997 collection, this volume not only offers a wider—and perhaps "queerer" perspective—on the study of language and masculinities, but also covers a broader geographical and socio-cultural spectrum, including work on Brazil, Israel, New Zealand, Singapore, and South Africa.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; masculinité; premier cycle; queer; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques; études de genres

Queer excursions: retheorizing binaries in language, gender, and sexuality - Zimman, Lal; Davis, Jenny L.; Raclaw, Joshua (Studies in language and gender, 2014)
Across scholarship on gender and sexuality, binaries like female versus male and gay versus straight have been problematized as symbols of the stigmatization and erasure of non-normative subjects and practices. The chapters of Queer Excursions offer a series of distinct perspectives on these binaries as well as on a number of other, less immediately apparent dichotomies that nevertheless permeate the gendered and sexual lives of speakers in various contexts. Some chapters focus on the limiting or misleading qualities of binaristic analyses, while others suggest that binaries are a crucial component of social meaning within particular communities of study. Rather than simply accepting binary structures as inevitable, or discarding them from our analyses entirely based on their oppressive or reductionary qualities, this volume advocates for a retheorization of the binary that affords more complex and contextually grounded engagement with speakers’ own orientations to dichotomous systems. It is from this perspective that contributors identify a number of diverging conceptualizations of binaries—including those that are non-mutually exclusive, those that liberate in the same moment that they constrain, those that are imposed implicitly by researchers, and those that recontextualize familiar divisions with innovative meanings. With each chapter having a perspective on locally salient linguistic practices that help constitute gender and sexuality in marginalized communities, what the contributions to Queer Excursions together demonstrate is that researchers must be careful to avoid the assumption that our own preconceptions about binary social structures will be shared by the communities we study.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; pol4105; premier cycle; queer; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques

Langage, genre et sexualité - Auger, Nathalie (Collection Langue et pratiques discursives, 2011)
L'objectif de cet ouvrage est d'examiner les liens complexes entre langage, genre et sexualité. En adoptant un positionnement résolument critique, qui met l'accent sur les aspects historique, politique et social des pratiques langagières, cet ouvrage part de l'idée que le genre et l'identité sexuelle sont avant tout des constructions sociales et idéologiques qui trouvent une forme de matérialité, entre autres, dans les discours et les pratiques sociales. Nous croyons que ces processus langagiers participent à la formation des différences et des inégalités - sans toutefois en être l'unique cause -, qu'ils contribuent à la réification des catégories au même titre qu'ils permettent d'en créer de nouvelles.--Résumé de l'éditeur.
Keywords: LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; europe; france; francophonie; féminisme matérialiste; identités LGBTQIA2+; langue; lin2685; linguistique; premier cycle; queer; québec; régions géographiques; sciences humaines; sexualité; sociolinguistique; thématiques

Reinventing identities: the gendered self in discourse - Bucholtz, Mary; Liang, A. C.; Sutton, Laurel A. (Studies in language and gender, 1999)
Talk is crucial to the way our identities are constructed, altered, and defended. Feminist scholars in particular have only begun to investigate how deeply language reflects and shapes who we think we are. This volume of previously unpublished essays, the first in the new series Studies in Language and Gender, advances that effort by bringing together leading feminist scholars in the area of language and gender, including Deborah Tannen, Jennifer Coates, and Marcyliena Morgan, as well as rising younger scholars. Topics explored include African-American drag queens, gender and class on the shopping channel, and talk in the workplace.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; intersectionnalité; lin2685; linguistique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

Gender articulated: language and the socially constructed self - Hall, Kira; Bucholtz, Mary (Routledge, 1995)
Gender Articulated is a groundbreaking work of sociolinguistics that forges new connections between language-related fields and feminist theory. Refuting apolitical, essentialist perspectives on language and gender, the essays presented here examine a range of cultures, languages and settings. They explicitly connect feminist theory to language research. Some of the most distinguished scholars working in the field of language and gender today discuss such topics as Japanese women's appropriation of "men's language," the literary representation of lesbian discourse, the silencing of women on the Internet, cultural mediation and Spanish use at New Mexican weddings and the uses of silence in the Anita Hill-Clarence Thomas hearings.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; maternité; premier cycle; queer; sciences humaines; sociolinguistique; thématiques; études de genres